Advanced Photonics 2016 (IPR, NOMA, Sensors, Networks, SPPCom, SOF) 2016
DOI: 10.1364/sensors.2016.sem4d.4
|View full text |Cite
|
Sign up to set email alerts
|

Curvature and shape distributed sensing using Brillouin scattering in multi-core fibers

Abstract: Distributed curvature and shape sensing using Brillouin scattering in multi-core fiber (MCF) is presented for the first time to the best of our knowledge, by exploiting bend-dependent Brillouin frequency shift (BFS) in off-center cores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In recent years, advancement of research on effect of bend on Brillouin scattering frequency shift in multicore fibres has introduced a novel principle for FOSSs, promising long range full 3D shape sensing [61][62][63][64]. The latest research study has experimentally demonstrated use of conventional Brillouin optical time-domain analysis (BOTDA) for a 1 kilometre long multicore fibre bend sensing; however, further work is required to develop it to a FOSS [61].…”
Section: Evolution Trendmentioning
confidence: 99%
“…In recent years, advancement of research on effect of bend on Brillouin scattering frequency shift in multicore fibres has introduced a novel principle for FOSSs, promising long range full 3D shape sensing [61][62][63][64]. The latest research study has experimentally demonstrated use of conventional Brillouin optical time-domain analysis (BOTDA) for a 1 kilometre long multicore fibre bend sensing; however, further work is required to develop it to a FOSS [61].…”
Section: Evolution Trendmentioning
confidence: 99%
“…The principle of the here proposed method for distributed shape sensing is based on the linear dependence that the BFS of off-center cores in MCFs shows on the fiber curvature 5 . In particular, when a MCF is bent at a given position, different tangential strains are locally induced in each of the lateral cores, thus leading to different variations of the BFS.…”
Section: Working Principlementioning
confidence: 99%
“…In fact, the unique feature of MCF, containing multiple spatially isolated and independently transmitted channels, also provides a platform for distributed sensing applications. Recently, we reported the observation of the bending-dependence of the Brillouin frequency shift (BFS) in off-center cores in a MCF 5 , revealing that the BFS varies with a linear dependence on the local fiber curvature (the reciprocal of bending radius). This has demonstrated the potential of MCFs for distributed curvature and shape sensing based on conventional Brillouin sensing interrogation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations